Importance of predictors of rehospitalisation in heart failure: A survey of heart failure experts - Betihavas, Vasiliki; Newton, P.; Frost, S.; Alexandrou, Evan; Macdonald, P.; Davidson, P. (Elsevier Australia, 2013)
Aims: We investigated the opinion of clinical experts and researchers involved in chronic heart failure disease management regarding the ranking of patient, provider and system factors that predict the risk of rehospitalisation. Methods: Item generation for the online survey was informed by a literature review and current risk prediction models. Consultation with experts was undertaken via a secure online survey platform. Invitations to participate in the 10 question online survey were sent through Listserves of professional nursing and medical associations within Australia and New Zealand. Results: Data were collected in August 2011. A total of 119 respondents completed the survey. Respondents ranged from researchers, registered nurses, cardiologists and allied health personnel. A mean importance score was used to rank risk factors for rehospitalisation. Risk factors that scored high for predicting the risk for rehospitalisation included poor adherence to medications (9.04) and prior hospitalisation for heart failure (8.33). Having private health insurance (4.8) and being female (4.9) scored lower in influencing rehospitalisation for adults with heart failure. Conclusions: No new risk factors were identified from the experts in predicting the risk of rehospitalisation. The survey results will contribute to the development of a nomogram to convey prognostic information related to adults with heart failure that will guide clinicians in management decisions.